ARTIFICIAL INTELLIGENCE APPLICATIONS IN A PANDEMIC COVID-19 - Krit, Salahddine, 1976-; Singh, Vrijendra; Elhoseny, Mohamed; Singh, Yashbir ([S.l.] : CRC PRESS, 2021)
COVID-19, a novel coronavirus pandemic has disrupted our society in many ways. Digital healthcare innovations are required more than ever before as we have come across myriad challenges during this pandemic. Scientists and developers are learning and nding ways to use arti cial intelligence applications and natural language processing to comprehend and tackle this disease. AI technologies are playing an important role in the response to the COVID-19 pandemic. Experts are using all possible tools to study the virus, diagnose individuals, and analyze the public health impacts. This book is a collection of some of the leading efforts related to AI and COVID-19 focused on nding how AI can be helpful in monitoring situations from early warnings, swift emergency responses, and critical decision-making. It discusses the use of machine learning and how it may help to reduce the impacts of this pandemic in conjunction with all other research and strategies going on. The book serves as a technical resource of data analytics and AI applications in tracking infectious diseases. It will serve academics, students, data scientists, medical practitioners, and those involved in managing a global pandemic. Features: Directs the attention to the smart digital healthcare system in this COVID-19 pandemic Simulates novel investigations and how they will be beneficial in understanding the pandemic Analyses the various issues related to computing, AI apps, big data analytic techniques, and predictive scienti skill gaps Explains some interesting and diverse types of challenges and data-driven healthcare applications
OCLC-licensed vendor bibliographic record.
Keywords: COVID-19 (Disease) -- Data processing; COVID-19 Pandemic, 2020- -- Data processing; Artificial intelligence -- Medical applications; COMPUTERS / Artificial Intelligence; MEDICAL / Public Health